2015
DOI: 10.3389/fneur.2015.00071
|View full text |Cite
|
Sign up to set email alerts
|

Rational Pharmacological Approaches for Cognitive Dysfunction and Depression in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is not a single entity but rather a heterogeneous neurodegenerative disorder. The present study aims to conduct a critical systematic review of the literature to describe the main pharmacological strategies to treat cognitive dysfunction and major depressive disorder in PD patients. We performed a search of articles cited in PubMed from 2004 to 2014 using the following MeSH terms (Medical subject headings) “Parkinson disease”; “Delirium,” “Dementia,” “Amnestic,” “Cognitive disorders,” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In addition, the possibility of cognitive deficits and PD dementia will confuse the understanding of the patient's affective state. In a meta-analysis of 11 controlled clinical trials for pharmacological treatments in PD depression between the years 2004 and 2014 (Sandoval-Rincon et al, 2015 ), rasagiline was found effective, but at the dose of 2 mg/day, which is higher than the usual dose of 1 mg daily for PD symptomatology.…”
Section: Treatment Of Depression With Mao Inhibitorsmentioning
confidence: 99%
“…In addition, the possibility of cognitive deficits and PD dementia will confuse the understanding of the patient's affective state. In a meta-analysis of 11 controlled clinical trials for pharmacological treatments in PD depression between the years 2004 and 2014 (Sandoval-Rincon et al, 2015 ), rasagiline was found effective, but at the dose of 2 mg/day, which is higher than the usual dose of 1 mg daily for PD symptomatology.…”
Section: Treatment Of Depression With Mao Inhibitorsmentioning
confidence: 99%
“…It seems to have beneficial effects on the control of both the early cardinal motor symptoms of PD and other disabling motor features emerging in later stages of the disease, such as postural instability. Furthermore, Ralago ® also appears to own the previously described ability of rasagiline to beneficially influence the severity of NMS in PD[12] [13]. Some previous studies have found that rasagiline may improve HRQoL[7] [31].…”
mentioning
confidence: 73%
“…However, worsening of PD, psychotic and behavioral symptoms, malignancy, stroke, and arthritis were also reported in rare cases [7] [8] [9]. Overwhelming its potential side-effects, rasagiline treatment could improve some of the NMS of PD such as depression, and cognitive impairment [12] [13], and it has also been supposed to be neuroprotective in animal models of neurodegeneration [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a common neurodegenerative disorder. It is characterized by progressive degeneration of dopaminergic neurons in the pars compacta of the substantia nigra and the loss of nerve terminals in the basal ganglia structures ( 1 , 2 ). The dopaminergic system is one of the most studied neurochemical systems because damage to nigrostriatal neurons is the most critical component in the pathophysiology of PD ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%